2018
DOI: 10.1186/s42269-018-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of exopolysaccharides from novel marine bacteria and anticancer activity against hepatocellular carcinoma cells (HepG2)

Abstract: Background: The aim of the current study based on the production and characterization of exopolysaccharides (EPSs) isolated from marine sediment of the Mediterranean and Red Seas is to study its cytotoxic activity against HepG2 cells. Results: Eleven isolates have the ability to produce EPSs and also decreased the viability of HepG2 cell line in different manners. The five most promising isolates that produce high yield of EPSs and high cytotoxicity were identified by 16S RNA as Brevundimonas subvibrioides MSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…In general, the molecular weight of the EPS synthesized by marine bacteria usually ranges from 100 to 500 kDa 60 . As it has been previously described, these polymers contain different relative ratios of monosaccharides of Glc, Man, Gal, GlcA, and GalA coordinated in a range of around 10 to compose repeating units 61 . Regarding polydispersity index (PDI), it has been reported that a low (between 1.0–1.5) PDI can be observed: this value is used as a measure of the broadness of the molecular weight distribution of a polymer.…”
Section: Eps Production By Marine Bacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the molecular weight of the EPS synthesized by marine bacteria usually ranges from 100 to 500 kDa 60 . As it has been previously described, these polymers contain different relative ratios of monosaccharides of Glc, Man, Gal, GlcA, and GalA coordinated in a range of around 10 to compose repeating units 61 . Regarding polydispersity index (PDI), it has been reported that a low (between 1.0–1.5) PDI can be observed: this value is used as a measure of the broadness of the molecular weight distribution of a polymer.…”
Section: Eps Production By Marine Bacteriamentioning
confidence: 99%
“…and Pseudomonas sp., have shown antitumor activity that is of medical interest 15,29,105,108 . For instance, Asker et al 61 . isolated several marine bacteria that produced EPS and decreased the viability of HepG2 cells in different manners when different concentrations of EPS were evaluated (125–1000 μg/mL).…”
Section: Biotechnological Applications Of Epsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can be deduced that the presence of xylose and galactose monomers is the first reason for the anticancer activity of the produced EPS. Another possible reason is the presence of sulphate groups in EPS, since it has been reported that sulphate groups increase the anticancer activity of polysaccharides 52,67,68 …”
Section: Resultsmentioning
confidence: 99%